PENERAPAN OMNIBUS LAW DALAM PENATAAN PERATURAN DAERAH TENTANG PAJAK DAN RETRIBUSI DAERAH - Robeith Al Faroh, Ahmad; Zeinudin, Moh.; Munir, Miftahul (JAS : Jurnal Ahwal Syakhshiyyah, 2023)
The aim of this legal research is to discuss the application of the omnibus law method in structuring regional regulations regarding levies. The research technique used in this exploration is a normative research method using primary legal materials, secondary legal materials and tertiary legal materials. research resulted that the application of the omnibus law method to taxes and levies includes East Java Province Regional Regulation Number 9 of 2011 concerning Regional Levy which revokes several levy provisions from other regional regulations, and Sleman Regency Regional Regulation Number 13 of 2007 which amends several regional regulations become a regional regulation. The implementation of the omnibus law in the Sleman Regency Regional Regulations regarding levies has become a legal umbrella for efforts to manage budgets and resources effectively and efficiently. Although there are still several challenges and criticisms regarding the regulation of levy rates, in general the use of the omnibus law method is recognized as an effective tool in drafting regional regulations. Keywords: Arrangement; Local regulation; Omnibus Law.